2013
DOI: 10.1016/j.jaci.2012.12.1036
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 Driven Neutrophil Recruitment to the Skin Is Essential for Allergic Skin Inflammation

Abstract: SummaryScratching triggers skin flares in atopic dermatitis (AD). We demonstrate that scratching of human skin, and tape stripping of mouse skin, causes neutrophil influx. This influx in mice was largely dependent on the generation of leukotriene B 4 (LTB 4 ) by neutrophils and their expression of the LTB 4 receptor BLT1. Allergic skin inflammation in response to epicutaneous (EC) application of ovalbumin to tape-stripped skin was severely impaired in Ltb4r1 −/− mice, and required expression of BLT1 on both T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
16
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
4
16
1
Order By: Relevance
“…This finding is consistent with previous studies implicating LTB 4 -BLT1 signaling in the pathogenesis of rheumatoid arthritis (40) and atopic dermatitis (41). Although our findings and a previous report (42) share common molecular components involved in neutrophil recruitment, they act in a different order.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies implicating LTB 4 -BLT1 signaling in the pathogenesis of rheumatoid arthritis (40) and atopic dermatitis (41). Although our findings and a previous report (42) share common molecular components involved in neutrophil recruitment, they act in a different order.…”
Section: Discussionsupporting
confidence: 93%
“…Most, if not all, of these immune functions are associated with the BLT1 receptor, with BLT2 generally more associated with cancer progression (9). Studies with BLT1-deficient mice have shown that LTB 4 plays a significant role in neutrophil infiltration, eosinophil and effector T cell recruitment, and IL-13 and IgE production (10)(11)(12)(13). LTB 4 in turn is a potent inducer of a variety of leukocyte signaling events, including Ca 2+ mobilization, activation of PI3K/protein kinase B signaling pathways, adhesion of granulocytes to endothelial cells, and neutrophil chemotaxis, degranulation, and reactive oxygen species production (2).…”
mentioning
confidence: 99%
“…LTB 4 in turn is a potent inducer of a variety of leukocyte signaling events, including Ca 2+ mobilization, activation of PI3K/protein kinase B signaling pathways, adhesion of granulocytes to endothelial cells, and neutrophil chemotaxis, degranulation, and reactive oxygen species production (2). These cell functions are essential immune responses; however, increased release of LTB 4 by inflammatory cells at the site of inflammation can influence the extent of the local inflammatory response (14), driving goblet cell hyperplasia, mucus hypersecretion, and airway hyperresponsiveness (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…20,21 Neutrophil recruitment is a hall mark of innate immune responses, 22 and innate recruitment of neutrophil to the skin through leukotriene B4 (LTB4) is critical for induction of subsequent allergic skin inflammation. 22,23 We recently reported that RWPE challenge induces CXCR2 and TLR4-dependent innate recruitment of activated neutrophils to the airways, and these recruited neutrophil are critical for induction of allergic sensitization and allergic airway inflammation. 6 In the present study, we extend our earlier observations by demonstrating a broad role of MD2 in induction of innate and allergic airway inflammation and allergic sensitization by CDE, RWPE and extracts of pollens from grasses, weeds and trees.…”
Section: Discussionmentioning
confidence: 99%